Menyoal Tentang Perkawinan Beda Agama dan Akibatnya terhadap Hak Waris di Indonesia - Agus Hermanto; Arif Fikri; Imam Nur Hidayat (Prodi Hukum Ekonomi Syariah (Muamalah), 2022)
Interfaith marriage is not a new problem in Indonesia, but a problem that often occurs in society, even though the laws and regulations on marriage have regulated it, in reality there are still such marriages in society. Like the marriage in Semarang, Central Java, which sparked a lot of debate among legal experts. What's interesting is how the interfaith marriage procession can be held solemnly, then what is the law, both legally and formally? The purpose of this study was to find scientific answers regarding interfaith marriages that occurred in Semarang, Central Java. This type of research is qualitative, by revealing the historical-philosophy of the socio-empirical reality that occurs in society with the form of normative studies. The results of this study indicate that the laws and regulations regarding marriage in Indonesia prohibit interfaith marriages, as well as the Compilation of Islamic Law (KHI) and MUI Fatwa Number: 4 /MUNAS/VII/MUI/8/2005 concerning Interfaith Marriage. The reality of marriages that have occurred so far, including in Semarang, Central Java, is that they are only registered in the Civil and Church Registry, but are not registered with the Marriage Registrar at the Office of Religious Affairs (KUA).